2020
DOI: 10.3928/1081597x-20200930-01
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Chromatic Aberration in Patients Implanted With Trifocal Diffractive Hydrophobic IOLs

Abstract: PURPOSE:To measure the in vivo longitudinal chromatic aberration (LCA) from the chromatic difference of focus (480 to 700 nm) using psychophysical methods in patients bilaterally implanted with a hydrophobic trifocal intraocular lens (IOL). METHODS:Psychophysical best focus was measured in both eyes at different wavelengths (480 to 700 nm) and at three different viewing distances (0.00, +1.75, and +3.50 diopters [D]) using a custom-developed polychromatic adaptive optics set-up provided with a supercontinuum l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 32 publications
(43 reference statements)
1
6
0
6
Order By: Relevance
“…Following phacoemulsification and IOL implantation, the amount of chromatic aberration is reduced compared to a phakic eye [ 18 ], which shows variability between IOL models. One differentiating factor is the spectral dispersion of biomaterials, which show varying levels of wavelength dependency for their refractive indices [ 19 ]. Another important factor is lens design, as the effects of chromatic aberration can be corrected through the diffractive principle [ 15 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Following phacoemulsification and IOL implantation, the amount of chromatic aberration is reduced compared to a phakic eye [ 18 ], which shows variability between IOL models. One differentiating factor is the spectral dispersion of biomaterials, which show varying levels of wavelength dependency for their refractive indices [ 19 ]. Another important factor is lens design, as the effects of chromatic aberration can be corrected through the diffractive principle [ 15 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…This behaviour is the key for chromatic aberration correction solutions combining refractive and diffractive elements. Given that POD F and POD F-GF have the same diffractive pattern but different material with different Abbe number , a different chromatic aberration behaviour can be expected 37,38 . Since AR works with infrared light to not stimulate accommodation, different AR reliability could be expected for POD F and POD F-GF.…”
Section: Discussionmentioning
confidence: 99%
“…Garzón et al 9 compared the refractive outcomes in eyes implanted with one of the two IOL models (48 with the POD F GF IOL and 49 with the POD F IOL) at 1-month post-surgery, using subjective and objective methods. Both models have the same optical design but use distinct materials, with different Abbe numbers, which may change the behavior of the chromatic aberration 17 , 18 and therefore the outcomes found using objective methods such as autorefractometers or wavefront aberrometers. They concluded that none of the objective methods were as reliable as subjective refraction, irrespective of the lens material, but the POD F GF objective values seem to differ less with subjective refraction than the POD F objective values.…”
Section: Discussionmentioning
confidence: 99%